The epistemological conflict in the narratives of elementary school textbooks (1908- 1924): islamic and secular insights into education - Açıkgöz, Betül. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2012., 2012)
This study elaborates on the penetration of the secular point of view to the primary school textbooks that were theoretically rooted in a religious tarbiyah philosophy in the Second Constitutional Period. On one hand, it seeks the secularizing vision of the new pedagogy on the school subjects faced the challenge of modern scientific thought that had gained strength throughout the nineteenth century. On the other, it argues that the adaptation of the scientific discourse to the religious tarbiyah, legitimized the hold of the religious view on education. Focusing on religion, history and civics instruction through textbooks, it examines epistemological inconsistencies and dissenting ideological opinions in the stateapproved school knowledge written by various authors. It illustrates the philosophy of education as evidenced in the curriculum of 1913 and highlights the alternative narratives of authors contrasting from one another and differentiating from the state guidelines. Thus it traces the discursive ideological standpoints in textbooks and offthe curriculum narratives which had both Islamist and ethno-secular propensities. The study provides answer to the question of where school texts contributed to the production and reinforcement of the Ottoman-Muslim nationalism, and on the other hand, to what extent they became tools for developing alternative school knowledge, opposing and transgressing the given guidelines of standardized curriculums. It reveals the reflections of the conflict between Islamic and secularist policy of the Unionist period through themes such as religion, history, national consciousness, homeland, civilization and backwardness.
Keywords: Islamic education -- Turkey.; Islam and secularism -- Turkey.; Education and state -- Turkey -- History -- 20th century.